Pelatihan Good Breeding Practice untuk Meningkatkan Produktivitas Kambing dan Pendapatan Ekonomi Peternak di Kelurahan Jambula, Kota Ternate: Good Breeding Practice Training to Increase Goat Productivity and Farmers’ Economic Income in Jambula Village, Ternate City - Hariyono, Dwi Nur Happy; Endrawati, Eny; Aji, Krishna (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Goats are a key livestock commodity, providing food and employment. Goat farming in Ternate City is generally semi-intensive, particularly in the Jambula sub-district. The challenges faced by goat farmers include limited knowledge and skills, a lack of technological expertise in selecting superior seeds and managing feed, low livestock productivity, and inadequate waste management. Therefore, the purpose of this community service activity is to provide outreach and training on the application of Good Breeding Practice (GBP) to increase livestock productivity and community income. The stages of the community service activity included surveys, outreach, training with practice, and monitoring and evaluation. All activities were successful and were attended by 18 farmers. The farmers actively participated in each stage of the activity. The training included the Village Breeding Center (VBC), the production of flushing feed, and compost. The farmers can utilize the resulting flushing feed and compost. The farmers were able to practice making flushing feed and compost independently. After the training, the farmers’ knowledge and skills in implementing GBP increased. Therefore, ongoing support is needed to ensure the implementation of GBP continues to run smoothly and achieve the desired goals.